New Universal Strain Software Accurately Assesses Cardiac Systolic and Diastolic Function Using Speckle Tracking Echocardiography. Issue 8 (22nd January 2014) - Kolias, Theodore J.; Hagan, Peter G.; Chetcuti, Stanley J.; Eberhart, Diane L.; Kline, Nicole M.; Lucas, Sean D.; Hamilton, James D.
<x xml:space="preserve">Abstract</x> Background We have developed new universal strain software (USS) that can be used to perform speckle tracking of any Digital Imaging and Communications in Medicine (DICOM) image, regardless of the ultrasound system used to obtain it. Methods Fifty patients prospectively underwent echocardiography immediately prior to cardiac catheterization. Biplane peak global longitudinal strain (GLS), peak systolic longitudinal strain rate (SSR), peak early diastolic longitudinal strain rate (DSR), and peak early diastolic circumferential strain rate (DCSR) were determined using conventional strain software (CSS) that uses raw data, and using the new USS applied to DICOM images. Results Universal strain software correlated with CSS for GLS (r = 0.78, P < 0.001), SSR (r = 0.78, P < 0.001), DSR (r = 0.54, P < 0.001), and DCSR (r = 0.43, P = 0.019). GLS and SSR using USS correlated with left ventricular ejection fraction (LVEF) (r = −0.67 and −0.71, respectively) as well as using CSS (r = −0.66 and −0.71). Patients with diastolic dysfunction had significantly lower DSR (0.61 vs. 0.87/sec, P = 0.02) and DCSR (0.89 vs. 1.23/sec, P = 0.03), and less negative GLS (−10.8 vs. −16.1%, P = 0.002) using USS in all patients, as well as among those with LVEF ≥ 50%. Receiver‐operating characteristic (ROC) analysis for detection of diastolic dysfunction revealed a sensitivity and specificity of 82% and 83% for DCSR < 1.09/sec (area under the curve [AUC = 0.80]) and 85% and 83% for GLS > −13.7% (AUC = 0.84) using USS. Conclusion Universal strain software can be used to accurately assess LV systolic and diastolic function using speckle tracking echocardiography.